2021
DOI: 10.7554/elife.61539
|View full text |Cite
|
Sign up to set email alerts
|

Ral GTPases promote breast cancer metastasis by controlling biogenesis and organ targeting of exosomes

Abstract: Cancer extracellular vesicles (EVs) shuttle at distance and fertilize pre-metastatic niches facilitating subsequent seeding by tumor cells. However, the link between EV secretion mechanisms and their capacity to form pre-metastatic niches remains obscure. Using mouse models, we show that GTPases of the Ral family control, through the phospholipase D1, multi-vesicular bodies homeostasis and tune the biogenesis and secretion of pro-metastatic EVs. Importantly, EVs from RalA or RalB depleted cells have limited or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
82
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(88 citation statements)
references
References 77 publications
3
82
1
2
Order By: Relevance
“…CRISPR-mediated knockout of RALB significantly increased orthotopic TNBC tumor growth in vivo, increased 3D invasion, and increased cell viability in both adherent and nonadherent culture conditions. Our findings are dissimilar from those reported in three recent studies where RALA and RALB were found to play similar roles in BC cell line models [ 20 , 21 ] or transient silencing of RALB was found to decrease BC cell line invasion [ 22 ]. In silico analyses utilizing the large TCGA and METABRIC breast cancer patient gene expression databases uncovered paradoxical associations between survival and RALA and RALB expression in support of our in vitro and in vivo findings.…”
Section: Introductioncontrasting
confidence: 99%
See 2 more Smart Citations
“…CRISPR-mediated knockout of RALB significantly increased orthotopic TNBC tumor growth in vivo, increased 3D invasion, and increased cell viability in both adherent and nonadherent culture conditions. Our findings are dissimilar from those reported in three recent studies where RALA and RALB were found to play similar roles in BC cell line models [ 20 , 21 ] or transient silencing of RALB was found to decrease BC cell line invasion [ 22 ]. In silico analyses utilizing the large TCGA and METABRIC breast cancer patient gene expression databases uncovered paradoxical associations between survival and RALA and RALB expression in support of our in vitro and in vivo findings.…”
Section: Introductioncontrasting
confidence: 99%
“…Additional studies will be needed determine if these disparate findings are the result of cell line-specific effects or due to differences in study design. It has also been reported [ 20 ] that elevated expression of both RALA and RALB are associated with poor outcome in the TCGA breast cancer patient cohort. Our findings confirm strong association between elevated RALA expression and poor outcome, but do not support a correlation between elevated RALB expression and reduced BC patient survival.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…For example, KIF20B overexpression in BC correlates with poor prognoses [ 27 ]. Similarly, RALA upregulation is a marker of poor prognosis in BC patients [ 28 ]. Notably, our analysis suggested that proteasome-related pathways may be affected by IFNγ signaling, implying that: 1) some proteasome inhibitors could be tested as pharmacological tools for different cancer types, including BC [ 29 , 30 ]; 2) proteasome subunit (as PSMD8 ) deregulation can result in cancer progression, and resistance to proteasome inhibitors [ 31 , 32 ]; 3) IFNγ increases ISGylation, a protein modification associated with protein stability by competing with the ubiquitination pathway in BC [ [33] , [34] , [35] ]; and 4) the IFNγ repression of proteolysis-associated genes may be helpful in the development of novel strategies to treat this pathology.…”
Section: Discussionmentioning
confidence: 99%
“…The exocytosis of the ILV-containing MVBs is mainly driven by Rab GTPases at the plasma membrane, specifically RAB27A and RAB27B. Ghoroghi et al identified RalA/B GTPases were a novel molecular mechanism that could control exosome secretion levels via the homeostasis regulation of MVBs 20 . The RalA/B-phospholipase D1 (PLD1)-phosphatidic acid (PA) axis governed exosome biogenesis to a certain extent.…”
Section: Factors Promoting Tumor-derived Exosome Biogenesis Release and Uptake For Bc Metastasismentioning
confidence: 99%